1995
DOI: 10.1007/bf00193728
|View full text |Cite
|
Sign up to set email alerts
|

Developmental patterns during direct somatic embryogenesis in protoplast cultures of european larch (Larix decidua Mill.)

Abstract: Protoplasts isolated from embryogenic suspension cultures of European larch (Larix decidua Mill.) were cultured in thin alginate layers using a nylon mesh to enable a monitoring of the development of single cells. The patterns of cell division and differentiation are characterized and compared with zygotic embryogenesis to which homologies can only be drawn to some extent when the protoplasts grow in an auxinfree environment. Already at 2.5 μM both 2,4-dichlorophenoxyacetic acid or indole-3-acetic acid cause v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Addition of 2,4-D into the culture medium promotes endogenous accumulation of IAA, which is positively associated with embryogenic competence. However, residual effects of 2,4-D have been associated with abnormal somatic embryo development during the maturation phase (Korlach and Zoglauer 1995;Guerra et al 2000;Silveira et al 2004a). These results suggest that PAs supplementation to cultures could enhance embryogenic potential for the further development of somatic embryos, as compared to untreated cultures.…”
Section: Resultsmentioning
confidence: 96%
“…Addition of 2,4-D into the culture medium promotes endogenous accumulation of IAA, which is positively associated with embryogenic competence. However, residual effects of 2,4-D have been associated with abnormal somatic embryo development during the maturation phase (Korlach and Zoglauer 1995;Guerra et al 2000;Silveira et al 2004a). These results suggest that PAs supplementation to cultures could enhance embryogenic potential for the further development of somatic embryos, as compared to untreated cultures.…”
Section: Resultsmentioning
confidence: 96%
“…In A. angustifolia, the cell proliferation in culture medium free of growth regulators can be a requisite for the subsequent embryonic development . It has been suggested that the presence of auxin in the culture medium influenced the formation of non polar proembryos affecting the development of somatic embryos in the maturation phase (Korlach & Zoglauer, 1995). In Pinus sylvestris, all developmental stages of somatic embryogenesis were observed in culture medium free of growth regulators (Lelu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In species such as Daucus carota L. (Michalczuk et al 1992) and Triticum aestiyum L. (Hess and Carman 1998), the IAA level must be kept to a very low concentration to ensure normal embryo formation. In coniferous species of L. decidua Mill., the embryogenic cultures will keep proliferating, rather than switching to a developmental phase, if the cultures contain a high amount of IAA (Korlach and Zoglauer 1995). It is apparent that endogenous IAA also plays an important role in controlling SE maturation in plant species.…”
mentioning
confidence: 99%